2008
DOI: 10.1158/1535-7163.mct-07-0540
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation of HMGA2: selective destabilization of promyelocytic leukemia protein via proteasome

Abstract: The HMGA2 architectural protein functions in a variety of cellular processes, such as cell growth, transcription regulation, neoplastic transformation, and progression. Up-regulation of HMGA2 protein is observed in many tumors and is associated with advanced cancers with poor prognoses. Although the expression and biochemical properties of HMGA2 protein are regulated by microRNA and phosphorylation, it is unknown whether HMGA2 activity can also be regulated by SUMOylation, and that is what is investigated in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Recently, it was reported that HMGA2 can be SUMOylated and that its SUMOylation is required to destabilize promyelocytic leukemia protein (21). In addition, Xenopus HMGB3 can be SUMOylated when it is overexpressed in the cell.…”
Section: High Mobility Group Nucleosomal Binding Domain 2 (Hmgn2)mentioning
confidence: 99%
“…Recently, it was reported that HMGA2 can be SUMOylated and that its SUMOylation is required to destabilize promyelocytic leukemia protein (21). In addition, Xenopus HMGB3 can be SUMOylated when it is overexpressed in the cell.…”
Section: High Mobility Group Nucleosomal Binding Domain 2 (Hmgn2)mentioning
confidence: 99%
“…Aside from phosphorylation, a study by Cao et al [62] showed that HMGA2 protein can undergo SUMOylation, which can lead to the degradation of promyelocytic leukemia (PML) protein via the ubiquitin-proteasomal pathway; interestingly, arsenic trioxide treatment can stimulate the SUMOylation of HMGA2 and the subsequent degradation of PML.…”
Section: Ptms Of Hmga Proteinsmentioning
confidence: 99%
“…Finally, another group has recently found that HMGA2, a member of a family of architectural proteins and regulators of gene transcription, also promotes PML degradation by the proteasome (Cao et al, 2008). Intriguingly, sumoylation is again brought into the picture because only sumoylated HMGA2 can promote PML degradation (Cao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, sumoylation is again brought into the picture because only sumoylated HMGA2 can promote PML degradation (Cao et al, 2008). Furthermore, arsenic trioxide stimulates HMGA2 sumoylation and the localization of HMGA2 in rings that surround PML-NBs (Cao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%